2010
DOI: 10.3917/mav.033.0035
|View full text |Cite
|
Sign up to set email alerts
|

Les apprentis de l'enseignement supérieur : de la satisfaction à l'engagement ?

Abstract: Distribution électronique Cairn.info pour Management Prospective Ed.. © Management Prospective Ed.. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
2
0
6
Order By: Relevance
“…Generally, the apprentices asked for more practice at school (e.g., "To have more practice in the theoretical courses"); in contrast, they rarely asked for more theory or complained about the training at the company. Moreover, the double logic in apprentices' perceptions of connections between the school and training company, as previously observed by Alves et al (2010) and Gurtner et al (2012), appeared to be confirmed. The school was seen as responsible for such links and was criticized for lacking connections with the training company.…”
Section: A Focus On the Connections Between School And Training Companysupporting
confidence: 72%
See 1 more Smart Citation
“…Generally, the apprentices asked for more practice at school (e.g., "To have more practice in the theoretical courses"); in contrast, they rarely asked for more theory or complained about the training at the company. Moreover, the double logic in apprentices' perceptions of connections between the school and training company, as previously observed by Alves et al (2010) and Gurtner et al (2012), appeared to be confirmed. The school was seen as responsible for such links and was criticized for lacking connections with the training company.…”
Section: A Focus On the Connections Between School And Training Companysupporting
confidence: 72%
“…They also have separate and distinctive visions of apprentices, with teachers seeing them as pupils at school and trainers seeing them more as workers at the training company. These two logics lead apprentices to experience two different forms of training in the two learning sites (Alves, Gosse, & Sprimont, 2010;Gurtner, Gulfi, Genoud, de Rocha Trindade, & Schumacher, 2012;Tynjälä, 2008). First, even if there are specific aims at the training company, the level of formality is much lower as the curriculum is less detailed and formalized than at the vocational school.…”
Section: The Swiss Dual System: Different Learning Sites Different Logicsmentioning
confidence: 99%
“…Ces diverses tensions des rôles dans le cadre professionnel ont des conséquences multiples. Les études d 'Alves et al (2010a'Alves et al ( , 2010b s'intéressent, dans le cadre de l'apprentissage en alternance en France, à l'impact des tensions de rôle (au sein de l'école et de l'entreprise formatrice, mais également entre les deux lieux) sur la satisfaction dans l'apprentissage, l'engagement et l'intention de rester dans l'entreprise après la formation. En ce sens, les auteur•e•s suggèrent que l'ambiguïté de rôle, tant au travail qu'à l'école, entretient un lien négatif avec la satisfaction qui, à son tour, est liée à l'engagement et à l'intention de rester dans l'entreprise formatrice (Alves et al, 2010b).…”
Section: Les Résultats Des Tensions De Rôle Caractérisant La Qualité En Fp : Auto-efficacité Engagement Satisfaction Et Intention De Résiunclassified
“…À ces éléments rendant principalement compte d'aspects institutionnels et formels de la formation professionnelle (FP) en alternance s'ajoute l'aspect subjectif du vécu des apprenti•e•s, qui s'avère central dans la définition de la qualité en formation professionnelle (Gross et al, 2020 ;Stalder & Carigiet Reinhard, 2014). Il s'agit notamment de tensions que les apprenti•e•s peuvent ressentir quant au(x) rôle(s) qu'elles et ils assument durant leur formation en école et en entreprise et qui constituent pour partie leur conception de la qualité (Alves et al, 2010b ;Wenger, sous presse).…”
Section: Introductionunclassified
“…Then, the key is for organizations to create a culture of mutual respect, promote the full participation of all workers, regardless of their rank or identity groups, and reward excellence. Alves et al (2010aAlves et al ( , b, 2013) works examine job satisfaction of French young apprentice in high education. They demonstrate that satisfaction concerning the apprenticeship is explained by satisfaction about the job and not by satisfaction about the school.…”
Section: Introductionmentioning
confidence: 99%